Secondary Sclerosing Cholangitis due to Severe COVID-19: An Emerging Disease Entity? - Seifert, Michael; Kneiseler, Guntje; Dechêne, Alexander (Digestion, 2023)
Introduction: Coronavirus disease 2019 (COVID-19) can lead to many extrapulmonary manifestations. In this case series, we report on 7 patients developing secondary sclerosing cholangitis (SSC) after severe COVID-19 with intensive care treatment. Methods: Between March 2020 and November 2021, 544 patient cases with cholangitis treated at a German tertiary care centre were screened for SSC. Patients found to be suffering from SSC were assigned to COVID-19 group if SSC presented after a severe course of COVID-19 and to non-COVID-19 group if not. Peak liver parameters as well as intensive care treatment factors and data generated from liver elastography were compared between both groups. Results: We identified 7 patients who developed SSC after a severe course of COVID-19. In the same period, 4 patients developed SSC due to other causes. Mean values of gamma-glutamyl transferase (GGT) and alkaline phosphatase (ALP) were higher in the COVID-19 group than in the non-COVID-19 group (GGT: 2,689 U/L vs. 1,812 U/L and ALP: 1,445 U/L vs. 1,027 U/L), whereas intensive care treatment factors were comparable in both groups. Only the mean duration of mechanical ventilation was shorter in the COVID-19 group than in the non-COVID-19 group (22.1 days vs. 36.7 days). Liver elastography indicated a fast progression to liver cirrhosis with a mean liver stiffness of 17.3 kilopascals (kPa) in less than 12 weeks in the COVID-19 group. Conclusions: Our data suggest a more severe course of SSC when caused by SARS-CoV-2. Reasons for this are probably multifactorial, including a direct cytopathogenic effect of the virus.
CRIS-Team WoS Importer:2023-04-07